Nutritional status of apple orchards in Rio Grande do Sul and Santa Catarina, Brazil - Freire, Claudio José da Silva; Anguinoni, Ibanor (Pesquisa Agropecuaria Brasileira, 2014)
This study was conducted to evaluate the nutritional status of twenty-seven Apple orchards, located in the State of Rio Grande do Sul and Santa Catarina, Brazil, using plant and soil analysis. Nitrogen, potassium, manganese and boron leaf contents were in the normal nutrition range. Phosphorus, calcium, magnesium, iron and copper were included in the low nutrition status; among these, calcium and magnesium were the most critical ones.
Keywords: foliar analysis; foliar diagnosis; plant nutrition